Bone diagenesis in via XVII inhumations (Bracara Augusta): Identification of taphonomic and environmental factors in differential skeletal preservation - Marado, Luís Miguel (2018)
Bone decomposition in archaeological contexts is differential and dependent on geological and taphonomic variables. The present work analyses evidences of skeletal diagenesis in 25 inhumations (3rd-4th to 5th-7th centuries) from the Via XVII necropolis of Bracara Augusta (Braga, Portugal). Bracara Augusta is located in the Minho region, Northwest Portugal. Minho’s granitic soils are characterized by high acidity. Precipitation is high in cold seasons and markedly reduced in the summer. The influence of these factors on bone preservation of Via XVII inhumations was analyzed through the comparison between graves with different structural traits (box presence, box material, sediment presence, chronology, coffin/stretcher presence or material, and cover presence or type), using the chi squared test. None of the comparisons showed significant differences in skeletal preservation frequencies. Yet, the comparison between graves that structurally limit skeletal contact with sediment (sealed/undisturbed boxes) or water flow (gable roof boxes) (100%) and the remaining graves (43.8%) presented significantly different frequencies (χ2 = 7.910; p = 0.005). The taphonomic conditions of Via XVII inhumations are inadequate for bone preservation. In graves preserving osteological material, the presence of a box structure is essential, yet only of determining influence if kept sealed or covered with a gable roof. The continued study of taphonomic factors influencing bone diagenesis will allow the preparation of archaeological excavations in Braga funerary contexts to account for the needed specialists and materials.